INFLUENCE OF MANAGEMENT COMPETENCE, UTILIZATION OF INFORMATION TECHNOLOGY AND STAKEHOLDER ENGAGEMENT ON ACCOUNTABILITY OF MANAGEMENT OF BOS FUNDS WITH TRANSPARENCY AS A MODERATING VARIABLE (Study on SMAN and SMKN in Aceh Selatan District) - Haniatun Haniatun; Islahuddin Islahuddin; Syukriy Abdullah (Research Collaboration Community (RCC), 2022)
The purpose of this study was to examine the effect of manager competence, utilization of information technology and stakeholder involvement on the accountability of BOS fund management with transparency as moderating. The study used a quantitative approach with the census method. The unit of analysis in this study was SMAN and SMKN in Aceh Selatan Regency, which were 38 schools with principals, treasurers, school committees and teachers as respondents. Data was collected by distributing questionnaires to 152 respondents. The results of the study indicate that the competence of managers, utilization of information technology, stakeholder involvement and accountability simultaneously affect the accountability of BOS fund management. Then, partially manager competence, use of information technology, stakeholder involvement, and transparency have a positive effect on the accountability of BOS fund management. Furthermore, transparency is able to moderate the relationship between the competence of managers and accountability for managing BOS funds. Transparency is able to moderate the relationship of stakeholder involvement to the accountability of BOS fund management. However, transparency is not able to moderate the relationship between the use of information technology and the accountability of BOS fund management.